Correlation of Adventitial Vasa Vasora Density with Intima-Media Thickness in Aorta of Cholesterol-Fed Rabbits - Shahid, Uzma; But, Shadab Ahmed; Athar, Zubia; Hafeez, Asma; Sarfraz, Rehmah (International Journal of Pathology, 2018)
Background: Atherosclerosis has been considered as the disease of intima with the role of tunica adventitiaso far neglected. Current evidence shows that adventitia, and particularly the vasa vasora (VV) reacts to theprocess of atherogenesis.Objective: The study was aimed to calculate the VV density in adventitia and to correlate it with intimamediathickness in aorta of cholesterol-fed rabbits.Materials & Methods: This experimental study was conducted in Army Medical College Rawalpindi. Samplesof vessels were obtained from twenty adult NZW rabbits fed normal (group A) or 2% high-cholesterol (groupB) diet for 6 weeks (n=10/group). Aortic sections were taken from each part (ascending, arch, descendingthoracic and abdominal) of every aorta. Light microscopic cross sectional analysis was performed in H&Estained slides. Intima-media thickness (IMT) and adventitial VV density were calculated and their correlationwas investigated in each part of aorta.Results: A total of 80 cross sections were analyzed. Mean±SE IMT and adventitial VV density wassignificantly increased in ascending, arch, and descending thoracic parts of group B versus their equivalentaortic parts in group A. But, there was an insignificant difference of means regarding VV density ofabdominal aorta between both groups, despite a significant increase of IMT in group B. A very strong positivecorrelation was observed between the adventitial VV density and IMT in each aortic part of cholesterol-fedrabbits.Conclusion: The present study showed that increased IMT is strongly associated with enhanced adventitialVV density in each aortic part of cholesterol-fed rabbits.